2002
DOI: 10.1159/000068567
|View full text |Cite
|
Sign up to set email alerts
|

N-(4-Hydroxyphenyl)-Retinamide Selectively Increases All-<i>Trans</i> Retinoic Acid Inhibitory Effects in <i>HER2/neu</i>-Overexpressing Breast Cancer Cells

Abstract: We previously reported that overexpression of the HER2/neu oncogene induces all-trans retinoic acid (ATRA) resistance in breast cancer cells. N-(4-hydroxyphenyl)-retinamide (4HPR), a synthetic analogue of ATRA, has been shown to repress the expression of HER2/neu and its family member, epidermal growth factor receptor (EGFR). We investigated whether 4HPR, by suppressing HER2/neu or EGFR expression, could sensitize breast cancer cells to ATRA. At 1.3 µM concentration (a clinically pharmacologically achievable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The ATRA/4-HPR combination has been examined in other cancer cells. Lim et al investigated whether 4-HPR (due to its suppression of HER2/neu and/or EGFR expression) sensitized breast cancer cells to ATRA, and found that at a concentration of 1.3 µM, 4-HPR increased ATRA sensitivity in a synergistic manner in BT-474, MDA-MB-453, and MCF-7/HER2 breast cancer cells (31). Another study demonstrated the efficacy of 4-HPR in mice bearing the human ovarian carcinoma IGROV-1, and demonstrated that 4-HPR significantly enhanced the antitumor activity of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…The ATRA/4-HPR combination has been examined in other cancer cells. Lim et al investigated whether 4-HPR (due to its suppression of HER2/neu and/or EGFR expression) sensitized breast cancer cells to ATRA, and found that at a concentration of 1.3 µM, 4-HPR increased ATRA sensitivity in a synergistic manner in BT-474, MDA-MB-453, and MCF-7/HER2 breast cancer cells (31). Another study demonstrated the efficacy of 4-HPR in mice bearing the human ovarian carcinoma IGROV-1, and demonstrated that 4-HPR significantly enhanced the antitumor activity of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon-g enhanced 4-HPR-mediated NO production in both ER-positive and ER-negative breast cancer cells, while tamoxifen increased 4-HPR-mediated NO production only in ER-positive cells [64]. Lim et al [76] reported that cyclosporin A increased the ability of 4-HPR to induce apoptosis in breast cancer cells, and this effect was correlated with increased NO production. Recently, NOSII-mediated NO production was found to be essential for the combination of 4-HPR and trastuzumab to induce apoptosis in HER2/neu-overexpressing breast cancer cells [77].…”
Section: Nitric Oxidementioning
confidence: 99%
“…MPT antagonists, such as cyclosporin A, rescued squamous carcinoma cells from the proapoptotic effects of 4-HPR [84]. In contrast, cyclosporin A increased the ability of 4-HPR to induce apoptosis in ER-positive and ER-negative breast cancer cells [76]. The role of MPT in 4-HPR-induced apoptosis in breast cancer cells has not been determined.…”
Section: Other Potential Mechanismsmentioning
confidence: 99%
“…Although Fitzgerald et al, demonstrated that the ER-negative, HER2/neu-positive cell-line SKBR3 was associated with high expression levels of RARA and response to retinoic acid (29), it appears that SKBR3 is an exception, with most of the work in this area concluding that the majority of the ATRAresistant cell-lines are associated with moderate to high levels of the HER2/neu protein (30)(31)(32). In addition, functional work has shown that high expression levels of HER2/neu are associated with resistance to ATRA (30,33), but that a synthetic analogue of ATRA, 4-hydroxyphenyl-retinamide (4HPR), can repress HER2/ neu expression, and thereby sensitise cells to ATRA.…”
Section: Discussionmentioning
confidence: 99%